ANALISIS DETERMINAN KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN PERSPEKTIF FRAUD DIAMOND THEORY (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2020) - Muhammad Tubagus Abbas; Herry Laksito (Diponegoro Journal of Accounting, 2022)
Financial statement fraud is an act that is intentionally carried out consciously by eliminating material information in the financial statements. Financial statement fraud causes losses to those who use financial statements and provides benefits to fraudsters. The purpose of this study is to examine the determinants of financial statement fraud using the fraud diamond theory perspective.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Purposive sampling was used as a sampling method. A total of 295 research data were used as research samples. Logistic regression analysis was used as a method of research analysis.The results of this study indicate that the determinants of financial statements fraud using the fraud diamond theory perspective which is represented by financial stability, external pressures, and change in directors have positive significant effect on financial statements fraud, while financial targets, effective of monitoring, nature of industry, change in auditor have no significant effect on financial statements fraud.